Academia in Conflict
XI, 133 p. 6 illus.
Keywords: "The book opens a new dialogue on theories and practices of crisis communication for its revolutionary emphasis on stakeholders instead of administration, on crisis transformation instead of crisis management." —Yong-Kang Wei, Professor, University of Texas Rio Grande Valley This book explores communication as a key influence on the trajectory of conflicts and crises in the specific context of academia. From the ideological responsibilities of academia to the profit-seeking motives of institutions, the authors explore challenges facing faculty across multiple disciplines. Critique of the higher education industry is more necessary than ever in the context of academic corporatization and marketization. Academia in Conflict reveals how institutional discourses can contribute to or mitigate conflict and crisis, offering communication practices that prioritize stakeholder experiences and needs. Enduring academic crises are addressed,including declines in public funding, mental health emergencies, and threats to job stability. Academia in Conflict provides crucial insights for navigating the challenges of higher education today. Adrienne P. Lamberti is Professor of Languages & Literatures at the University of Northern Iowa, where she coordinates its Professional Writing Program. She has published extensively on the rhetoric of professional and technical communication. Anne R. Richards is Professor of English at Kennesaw State University, where she has directed the peace studies and religious studies programs and where she helped found the PhD program in International Conflict Management.